Highly Sensitive Multifilament Fiber Strain Sensors with Ultrabroad Sensing Range for Textile Electronics - Lee, Jaehong; Shin, Sera; Lee, Sanggeun; Song, Jaekang; Kang, Subin; Han, Heetak; Kim, SeulGee; Kim, Seunghoe; Seo, Jungmok; Kim, DaeEun; Lee, Taeyoon (AMER CHEMICAL SOC, 2018)
Highly stretchable fiber strain sensors are one of the most important components for various applications in wearable electronics, electronic textiles, and biomedical electronics. Herein, we present a facile approach for fabricating highly stretchable and sensitive fiber strain sensors by embedding Ag nanoparticles into a stretchable fiber with a multifilament structure. The multifilament structure and Ag-rich shells of the fiber strain sensor enable the sensor to simultaneously achieve both a high sensitivity and largely wide sensing range despite its simple fabrication process and components. The fiber strain sensor simultaneously exhibits ultrahigh gauge factors (similar to 9.3 x 10(5) and similar to 659 in the first stretching and subsequent stretching, respectively), a very broad strain-sensing range (450 and 200% for the first and subsequent stretching, respectively), and high durability for more than 10 000 stretching cycles. The fiber strain sensors can also be readily integrated into a glove to control a hand robot and effectively applied to monitor the large volume expansion of a balloon and a pig bladder for an artificial bladder system, thereby demonstrating the potential of the fiber strain sensors as candidates for electronic textiles, wearable electronics, and biomedical engineering.
Keywords: PRINTABLE ELASTIC CONDUCTORS; EPIDERMAL ELECTRONICS; ELECTRIC-CIRCUITS; HIGH-CONDUCTIVITY; HUMAN-MOTION; SUPERCAPACITORS; SKIN